2002
DOI: 10.1182/blood.v99.8.2985
|View full text |Cite
|
Sign up to set email alerts
|

Recurring chromosomal abnormalities in leukemia inPML-RARA transgenic mice parallel human acute promyelocytic leukemia

Abstract: Acute promyelocytic leukemia (APL) is characterized by the t(15;17)(q22;q11.2), which results in the PML-RARA fusion gene. In previous studies, we demonstrated that expression of a human PML-RARA complementary DNA in murine granulocyte precursor cells initiated the development of leukemia. However, leukemogenesis by PML-RARA required additional genetic alterations. To identify genetic changes that cooperate with PML-RARA in leukemogenesis, we performed spectral karyotyping analysis of myeloid leukemias from hM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
2
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 31 publications
6
73
2
2
Order By: Relevance
“…Table 2 Ingenuity Systems genetic networks affected by Ara-C resistance The JAK2 1849G4T mutation results in valine to phenylalanine substitute at 617 amino acid (JAK2 V617F ), and this molecular change occurs in most patients with polycythemia vera (PV) and in approximately 50% of patients with essential thrombocythemia (ET) or chronic idiopathic myelofibrosis (CIMF). [1][2][3][4] Mitotic recombination at the terminal portion of the 9p region is considered to produce homozygous JAK2 V617F , and approximately 20-30% of PV patients have homozygous JAK2 V617F whereas most ET patients have heterozygous JAK2 V617F3 . However, it is still controversial whether JAK2 V617F is a primary genetic event in CMPD, and the frequency of homozygous JAK2 V617F varied in different reports, probably owing to technical differences or diagnostic criteria.…”
Section: Gene Namementioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 Ingenuity Systems genetic networks affected by Ara-C resistance The JAK2 1849G4T mutation results in valine to phenylalanine substitute at 617 amino acid (JAK2 V617F ), and this molecular change occurs in most patients with polycythemia vera (PV) and in approximately 50% of patients with essential thrombocythemia (ET) or chronic idiopathic myelofibrosis (CIMF). [1][2][3][4] Mitotic recombination at the terminal portion of the 9p region is considered to produce homozygous JAK2 V617F , and approximately 20-30% of PV patients have homozygous JAK2 V617F whereas most ET patients have heterozygous JAK2 V617F3 . However, it is still controversial whether JAK2 V617F is a primary genetic event in CMPD, and the frequency of homozygous JAK2 V617F varied in different reports, probably owing to technical differences or diagnostic criteria.…”
Section: Gene Namementioning
confidence: 99%
“…2,3 To characterize the sensitive and resistant lines, their chromosomal features were examined using spectral karyotyping analysis as described previously. 4 It is known that cell lines tend to manifest chromosomal abnormalities, especially after an extensive passaging process. As expected, both Ara-C-sensitive and -resistant cells show multiple chromosomal alterations, including chromosome loss, translocation and amplification (data not shown).…”
mentioning
confidence: 99%
“…37 Such an approach would permit one to study the exact contribution of each known genetic alteration to the induction of the leukemic phenotype without the background of chromosomal aberrations acquired during the development of late-onset leukemia in the PML/ RARa-transgenic mice. [38][39][40] PML/RARa and the differentiation of HSC Grignani et al 41 showed that PML/RARa enables human CD34 þ /linÀ cells to reach the promyelocytic level of differentiation but not to go further along the erythroid or the thrombocytic lineage, even if cells are cultivated in an adequate cytokine cocktail. These data strongly suggest a global differentiation block, which functions -at least for the erythroid and thrombocytic lineages -already at a very early level, whereas the granulocytic precursors are blocked at a later stage of differentiation: at the promyelocytic level.…”
Section: Which Is the Leukemia-initiating Cell In Apl?mentioning
confidence: 99%
“…We carried out cytogenetic and SKY analysis on spleen or bone marrow cells as described previously 11 .…”
Section: Flow Cytometrymentioning
confidence: 99%